Radon and Thoron; Radioactive Gases Lurking in Earthen Houses in Rural Kenya - Chege, Margaret; Hashim, Nadir; Nyambura, Catherine; Mustapha, Amidu; Hosada, Masahiro; Tokonami, Shinji (Frontiers in Public Health, 2019)
In this paper, documented studies on radon and thoron concentrations in earthen dwellings and 238U and 232Th concentrations in soil in Kenya are reviewed. High concentrations of the isotopes were recorded in the earthen dwellings despite being generally well ventilated. Mrima Hill in the Coast region recorded the highest thoron levels with a mean of 652 Bq m-3. 25 % of dwellings had thoron concentration in excess of 1000 Bq m-3. Notably high indoor radon levels were recorded in Taita Taveta also in the Coast region, and in Kenyatta University situated in Nairobi in the Central region of the country. Radon concentration in the Rift Valley region was found to be too low to contribute significantly to radiation exposure. Based on studies on the concentration of 238U and 232Th in soil, the Southwestern region of the country was anticipated to have elevated radon/thoron concentrations in earthen dwellings. Existing studies involving measurement of indoor radon and thoron, and 226Ra and 232Th in soil are relatively few and of a small scale. More extensive studies are therefore necessary not only to corroborate the risk projections but to also generate sufficient data to enable countrywide mapping of indoor radon/thoron risk-prone areas.